(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Splenic notches are important landmark for the clinician to differentiate enlarged spleen from left kidney during abdominal palpation. Notches are usually present in the upper/superior border of spleen which represents the lobulated development from the left wall of dorsal mesogastrium and fuses with progress of age. Objective: To find out the incidence, position, number of splenic notches and fissure in Bangladeshi cadaver. Methods: This descriptive cross sectional study was done from July 2007 to June 2008 on 120 formalin fixed cadaveric human spleens in the department of Anatomy at Mymensingh Medical College, Mymensingh. Results: : In the present study, splenic notches were found in 85% of cases. In relation to sex the notches were found in 86.2% of male and 81.81% of female cadaver. In upper border notches were found in 84% of cases which were 1-7 in number. In lower border notches were present in 36.67% of spleens and are 1-3 in number. Spleenic fissure was found in 9.19% of male and 9.09% of female spleen. Conclusion: Adequate knowledge of splenic morphology will be helpful for the clinical diagnosis of splenic disease. JAFMC Bangladesh, Vol 21, No 1 (June) 2025: 12-15